Exhalation of alternative tobacco product aerosols differs from cigarette smoke—and may lead to alternative health risks. (4th January 2022) - Karey, Emma; Reed, Taylor; Katsigeorgis, Maria; Farrell, Kayla; Hess, Jade; Gibbon, Grace; Weitzman, Michael; Gordon, Terry
Background: Variation in alternative tobacco product (ATP) constituents, heating potential, and consumer behaviors have made it difficult to characterize their health risks. To date, most toxicity studies of ATPs have used established cigarette endpoints to inform study design. Furthermore, to assess where ATPs fall on the tobacco harm continuum, with cigarettes representing maximum potential risk, studies have tended to compare the relative biological responses to ATPs against those due to cigarettes. Objectives: 1) To characterize the exhalation profiles of two popular ATPs: electronic cigarettes (e-cigarettes) and hookah waterpipes (hookah) and 2) to determine if ATP exhalation patterns were representative of cigarette exhalation patterns. Methods: Exhalation patterns were recorded (mouth only, nose only, or both mouth and nose) among individuals observed in the New York City tri-state area using a recognizable tobacco product (cigarette, e-cigarette, or hookah). Cigarette smokers and e-cigarette vapers were observed on city streets; water-pipe smokers were observed inside Manhattan hookah bars. Results: E-cigarette vapers practiced exclusive nasal exhalation at far higher rates than did cigarette smokers (19.5% vs 4.9%). Among vapers, e-cigarette device type was also significantly associated with exhalation profile. Overall, cigarette smokers exhaled from their nose approximately half to one-third as often as ATP users (hookah and e-cigarettes, respectively). Conclusions: Nasal exhalation of tobacco emissions appears to be a shared characteristic across several types of ATPs. It is therefore plausible that ATP-specific consumer behaviors may foster unique upper respiratory health consequences that have not been observed in smokers. Thus, product-specific behaviors should inform the prioritization of biological endpoints used in studies evaluating ATP toxicity and health effects.